Ranibizumab in neovascular age-related macular degeneration: a 5-year follow-up - Cvetkova NP (Dove Medical Press, 2016)
Nadezhda P Cvetkova, Kristina Hölldobler, Philipp Prahs, Viola Radeck, Horst Helbig, David Märker Department of Ophthalmology, University of Regensburg, Regensburg, Germany Purpose: Our aim was to evaluate an optical coherence tomography (OCT) and visual acuity (VA)-guided, variable-dosing regimen with intravitreal ranibizumab injection for treating patients with neovascular age-related macular degeneration (AMD) from 2007 to 2012. Design: This was a retrospective clinical study of 5 years follow-up in a tertiary eye center. Patients and methods: In this study, 66 patients with neovascular AMD (mean age of 74 years, SD 8.7 years) were included. We investigated the development of best-corrected visual acuity (BCVA), the number of intravitreal injections, and the central retinal thickness measured with OCT (OCT Spectralis) over 5 years of intravitreal treatment. Results: The mean number of intravitreal ranibizumab injections over 5 years was 8.8. The mean BCVA before therapy was 0.4 logarithm of the minimum angle of resolution (logMAR). After 5 years of therapy, the mean BCVA was 0.6 logMAR. In all, 16% of treated patients had stable VA over 5 years and 10% of study eyes approved their VA. The mean OCT-measured central retinal thickness at the beginning of this study was 295 µm; after 5 years of treatment, the mean central retinal thickness was 315 µm. There was an increase in central retinal thickness in 47.5% of examined eyes. Conclusion: Other studies showed VA improvement in OCT-guided variable-dosing regimens. Our study revealed a moderate decrease in VA after a total mean injection number as low as 8.8 injections over 5 years. In OCT, an increase in central retinal thickness over 5 years could be observed. Probably, this is due to deficient treatment when comparing the total injection number to other treatment regimens. Anti-VEGF therapy helps to keep the VA stable for a period of time, but cannot totally stop the progression of the disease completely. Patients with late stages of neovascular AMD can maintain VA even if they are relatively undertreated. Keywords: AMD, neovascular, OCT, ranibizumab, retina